2020
DOI: 10.1152/ajpheart.00357.2019
|View full text |Cite
|
Sign up to set email alerts
|

Regional right ventricular function in rats: a novel magnetic resonance imaging method for measurement of right ventricular strain

Abstract: The function of the right ventricle (RV) is linked to clinical outcome in many cardiovascular diseases, but its role in experimental heart failure remains largely unexplored due to difficulties in measuring RV function in vivo. We aimed to advance RV imaging by establishing phase-contrast MRI (PC-MRI) as a robust method for measuring RV function in rodents. A total of 46 Wistar-Hannover rats with left ventricular (LV) myocardial infarction and 10 control rats (sham) were examined 6 wk after surgery. Using a 9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Pulmonary congestion resulted in higher longitudinal strain at about −10.1% and −13.8% circumferentially. Global strain rate showed a similar trend with circumferential and longitudinal strain rates of −4 s −1 and −4.7 s −1 , respectively [93].…”
Section: Small Animal Modelssupporting
confidence: 60%
“…Pulmonary congestion resulted in higher longitudinal strain at about −10.1% and −13.8% circumferentially. Global strain rate showed a similar trend with circumferential and longitudinal strain rates of −4 s −1 and −4.7 s −1 , respectively [93].…”
Section: Small Animal Modelssupporting
confidence: 60%
“…Cine segmentation was performed using Segment v3.0 R7820 (http://segment.heiberg.se). 13 Tissue phase mapping (TPM) slices were acquired, one mid‐ventricular short axis and one long axis, allowing calculation of systolic and diastolic strains and strain rates as previously described 14,15 . Combination of TPM with data from echocardiography allowed calculation of the ratio of early mitral inflow velocity to the global diastolic strain rate (E/e'SR).…”
Section: Methodsmentioning
confidence: 99%
“…13 Tissue phase mapping (TPM) slices were acquired, one mid-ventricular short axis and one long axis, allowing calculation of systolic and diastolic strains and strain rates as previously described. 14,15 Combination of TPM with data from echocardiography allowed calculation of the ratio of early mitral inflow velocity to the global Sacubitril/valsartan ameliorates cardiac hypertrophy and diastolic dysfunction in cardiac pressure overload diastolic strain rate (E/e'SR). Data were analysed in a blinded fashion using MATLAB (The MathWorks Inc., USA).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Previous studies have shown that cardiac dysfunction reduces LS [13]. MR myocardial strain analysis using tagging and phase contrast has also been used to evaluate local myocardial wall motion in rodents [14,15]. However, these methods have a problem in that the examination time is extended since it is necessary to acquire a tagging image and a phase-contrast image.…”
Section: Introductionmentioning
confidence: 99%